2007
DOI: 10.1016/j.rmed.2006.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of pulmonary histoplasmosis to sarcoidosis: A case report

Abstract: Histoplasmosis, a dimorphic fungus, and sarcoidosis, a disease of unknown etiology, share many clinical features, including typical manifestations of granulomatous inflammation involving the lungs and mediastinal lymphatics in association with constitutional symptoms. As such, they are often difficult to distinguish based upon clinical presentation. Recent studies suggest that sarcoidosis may be triggered by infectious agents. Here we present a case of documented pulmonary histoplasmosis that evolved into sarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…He suggested that histoplasmosis could be the primary disease and stimulate the sarcoidosis [ 10 ]. Wynbrandt and Crouser described a case in which documented pulmonary histoplasmosis allegedly evolved into sarcoidosis [ 11 ]. Interestingly, there seems to be a higher prevalence of sarcoidosis in Franklin County, Ohio (the demographic profile of which is nearly identical to that of the US) [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…He suggested that histoplasmosis could be the primary disease and stimulate the sarcoidosis [ 10 ]. Wynbrandt and Crouser described a case in which documented pulmonary histoplasmosis allegedly evolved into sarcoidosis [ 11 ]. Interestingly, there seems to be a higher prevalence of sarcoidosis in Franklin County, Ohio (the demographic profile of which is nearly identical to that of the US) [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in response to deforestation and urbanization, bats populations are adapting and setting up in the anthropized rural and urbanized environments, closer to human dwellings, leading to shift in the pattern of disease outbreaks to cover urban areas as well, with the number of infected individuals exceeding that found in rural areas (Jung and Threlfall 2018;Deepe Jr 2018). Though most of these infections are clinically silent and resolve without any c o n s e q u e n c e i n i m m u n o c o m p e t e n t i n d iv i d u a l s , H. capsulatum has been known to be behind such unusual cases as puzzling sickness of the pastor that cleaned copious amounts of bat guano from belfry of the church (Wynbrandt and Crouser 2007), outbreak of an unknown severe febrile illness of workers in the Dominican Republic tasked with cleaning accumulated bat guano from access tunnels to a hydroelectric dam inhabited by large bat colonies (Armstrong et al 2018) or an outbreak affecting American tourists in a hotel in Acapulco (Guerrero, Mexico) where hotel's ornamental potted plants, fertilized with guano compost, were determined as the infectious source (Taylor et al 2005). In the period from 1938 to 2013, a total of 105 outbreaks involving 2.850 cases were reported in 26 states and the territory of Puerto Rico (Benedict and Mody 2016).…”
Section: Histoplasma Capsulatummentioning
confidence: 99%